Proceso contable de la microempresa Perno Repuesto Jehová Shalom de la parroquia San Juan durante el periodo 2021. - León Alvario, Dayaneth Yimabell (2022)
There are various actions that must be taken into account within an entity, it is important that each company, in order to carry out correct and optimal accounting, must have its expenses updated, tax payments, this makes the accounting process more reliable. The great importance of carrying out an accounting process is that it allows us to identify what type of transaction is being executed and then make a correct record in the system that is being used and identify the group of accounts in our chart of accounts it belongs to. This case study is oriented towards the accounting process of the micro-enterprise Perno Repuestos Jehovah Shalom, which lacks an adequate accounting structure to direct its activities. The development of this work had the purpose of obtaining information from the financial statements through financial ratios to determine that the non-implementation of an accounting system affects the profitability of the entity. For this, the entire accounting process was analyzed in order to identify problems in its structure. For the data collection, the techniques of survey directed to the accounting assistants and interview directed to the administrator were used. From the study of the data, it was concluded that the entity lacks a correct control in its operations, leading to errors when doing the accounting processes.